Effect of sulfate on crystal phase transition and crystal growth of titanium dioxide in metatitanic acid calcination. (4th May 2021) - Chen, K.; Yan, X. H.; Wu, P. S.; Wang, Z. N.; Wu, B.; Lin, F. R.
ABSTRACT: In order to investigate the effect of sulfate in metatitanic acid on crystal transition and crystal growth of TiO2 during the calcination of metatitanic acid from sulfate process, ammonia was used to remove sulfate in metatitanic acid in this study. TG-DTA, XRD and SEM were used to analyse the crystal phase transition and crystal morphologies. Experiments showed that removal of sulfate will be beneficial to crystal transition and growth. In calcination of desulfurized metatitanic acid, both the solid-state crystallization and the phase transition from anatase to rutile have been advanced by 50°C as compared to the control samples without desulfurization treatment. Moreover, the temperature can be reduced by 60°C to achieve the same rutile conversion rate of 97.6%, and the particle size can be reduced by 70 nm. The reduction in calcination temperature greatly alleviates the sintering tendency of TiO2 and aid to produce TiO2 crystals of even size.